THE ANALYSIS OF MAXIM VIOLATION IN ALL THE BRIGHT PLACES THE MOVIE - Beta Setiawati; Angelika Jeana Rachel; Ahnaf Dzaky Kamaluddin; Sholiyah Sholiyah; Alyssa Nur Rochmah (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2024)
This research analyzes maxim violation in the film All the Bright Places (2020). This movie talks about mental health, family, and relationships. The purpose of this research is to find what maxim violations are used in the movie All the Bright Places. The research method used is Descriptive Qualitative by using Grace Theory. The researcher analyzes the data thoroughly, with observations to find data results with explanations that will be compiled in the form of conversational dialogue. This study identifies the maxim violations of quality, quantity, relevance, and manner in the dialog between the main characters, Theodore Finch and Violet Markey. In this study, 9 violations of maxim quality, 3 violations of maxim quantity, 13 violations of maxim relevance and 6 violations of maxim manner were found.